2013
DOI: 10.1089/ham.2012.1065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Residence at Moderate Versus Low Altitude on Reducing Acute Mountain Sickness in Men Following Rapid Ascent to 4300 m

Abstract: To determine if residence at moderate (~2000 m) compared to low (<50 m) altitude reduces acute mountain sickness (AMS) in men during subsequent rapid ascent to a higher altitude. Nine moderate-altitude residents (MAR) and 18 sea-level residents (SLR) completed the Environmental Symptoms Questionnaire (ESQ) at their respective baseline residence and again at 12, 24, 48, and 72 h at 4300 m to assess the severity and prevalence of AMS. AMS cerebral factor score (AMS-C) was calculated from the ESQ at each time poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…We deem it unlikely that differences in experimental setup are sufficient to account for these discrepant findings between the three studies. An alternative explanation is the potential influence of (partial) altitude acclimatization [30] . Subudhi et al, [15] examined the effect of CO 2 clamping on competitive cyclists living and training at 1,650 m, therefore already acclimatized to exercise at moderate altitude.…”
Section: Discussionmentioning
confidence: 99%
“…We deem it unlikely that differences in experimental setup are sufficient to account for these discrepant findings between the three studies. An alternative explanation is the potential influence of (partial) altitude acclimatization [30] . Subudhi et al, [15] examined the effect of CO 2 clamping on competitive cyclists living and training at 1,650 m, therefore already acclimatized to exercise at moderate altitude.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also found that the extent of the erythropoietic response to altitude is dependent on the initial red cell volume [8] with attenuated increases in individuals with high initial red cell volumes. In a similarmanner, other studies reported that moderate-altitude residents starting with a 6%-13%higher [Hb] than sea-level residents demonstrate an attenuated increase in [Hb] as a result of exposure to a higher altitude[27,45]. The rough correction factors only consider one initial starting level of [Hb] and Hct for both men and women.…”
mentioning
confidence: 78%
“…Bedeutsame Akklimatisationseffekte und wesentlich bessere Verträglichkeit eines Höhenanstiegs werden durch Voraufenthalte in Höhenlagen um etwa 2000 m berichtet [6], aber auch Aufenthalte in simulierter Höhe (Höhenräume in Tallage) können unter bestimmten Voraussetzungen zu Akklimatisationszwecken genutzt werden.…”
Section: Häufigkeit Von Höhenbeschwerdenunclassified
“…Neben den erwähnten Akklimatisationsempfehlungen vor Ort, kann auch die "Vorakklimatisation" vor der Durchführung von bergsportlichen Aktivitäten in größeren Höhen eine besondere Rolle spielen [4,6]. Literatur…”
Section: Häufigkeit Von Höhenbeschwerdenunclassified